A Review of Exterior Waterproofing Technologies in Prefabricated Buildings - Liao Baiheng; Zhou Meng; Wang Yutong; Wu Zhiduo (E3S Web of Conferences)
This paper analyses the status quo of exterior wall waterproofing technology of prefabricated building, introduces the application of waterproofing coil laying, sealant waterproofing, grouting method, exterior wall waterproofing coating, waterproof concrete and the integration technology of heat preservation and drainage, and analyses their advantages and disadvantages. In the future, the research and application of new materials should be strengthened, and the effects of different waterproof technologies should be quantitatively compared through experiments to further improve the waterproof performance of prefabricated building external walls.